2017
DOI: 10.1002/cjoc.201700576
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Aerobic Oxidation of Aldehydes: Single Component Catalyst and Mechanistic Studies

Abstract: An aerobic oxidation of aldehydes towards carboxylic acids in MeCN using 1 atm of pure oxygen or oxygen in air as the oxidant and a catalytic amount of single component catalyst, Fe(NO3)3·9H2O, has been developed. Carboxylic acids with different synthetically useful functional groups were obtained at room temperature. Two mechanistic pathways have been proposed based on isotopic labeling, NMR monitoring, and control experiments. The practicality of this reaction has been demonstrated by conducting several 50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Then Au-catalyzed cycloisomerization of ( R a )- 4ja generated γ-butyrolactone bearing a trans C=C bond ( S , E )- 5ja in 95% yield with 91% ee and 98:2 of E / Z selectivity 24 . After sequential hydrogenation of ( S , E )- 5ja and Fe-TEMPO-catalyzed aerobic oxidation 60,61 of the resulting hydrogenated product without purification, ( R )-traumatic lactone was afforded in 67% yield with 98% ee by one time recrystallization.
Fig. 4The first enantioselective synthesis of ( R )-traumatic lactone.
…”
Section: Resultsmentioning
confidence: 99%
“…Then Au-catalyzed cycloisomerization of ( R a )- 4ja generated γ-butyrolactone bearing a trans C=C bond ( S , E )- 5ja in 95% yield with 91% ee and 98:2 of E / Z selectivity 24 . After sequential hydrogenation of ( S , E )- 5ja and Fe-TEMPO-catalyzed aerobic oxidation 60,61 of the resulting hydrogenated product without purification, ( R )-traumatic lactone was afforded in 67% yield with 98% ee by one time recrystallization.
Fig. 4The first enantioselective synthesis of ( R )-traumatic lactone.
…”
Section: Resultsmentioning
confidence: 99%
“…[12] Ma and co-workers found that a threecomponent catalyst (TEMPO, Fe(NO 3 ) 3 •9H 2 O and KCl) enabled room-temperature aerobic oxidation of primary alcohols to carboxylic acids in 1,2-dichloroethane (Scheme 1d), [13] in which Fe(NO 3 ) 3 •9H 2 O catalyzed further oxidation of aldehydes to carboxylic acids. [14] From the perspective of green and sustainable Laccase coupled with 2,2,6,6-tetramethylpiperidinyl-1-oxy (TEMPO) is a wellknown catalytic system for the oxidation of alcohols to the carbonyl compounds. In this work, a simple yet effective solvent engineering strategy is developed to enable aromatic alcohols/aldehydes to be efficiently oxidized to carboxylic acids by a laccase-TEMPO system.…”
mentioning
confidence: 99%
“…Although aerobic oxidation of aldehydes can be performed without catalysts, numerous homogeneous catalysts have been described for this particular reaction and, in particular, first-row transition metals . Recently, Y.-B.…”
mentioning
confidence: 99%